Karakter Agronomi dan Daya Hasil Tiga Klon Ubi Jalar Ungu (Ipomoea batatas) di Lahan Masam Lampung - Dewi, Ratna; Sutrisno, Hery (Jurnal Penelitian Pertanian Terapan, 2014)
Sweet potato is one of the alternative foods of rice that can be grown on a variety of soil conditions and almost fits on all altitude. Sweet potato clones with purple tuber contains anthocyanins which are antioxidants for our bodies. Purple sweet potato clones include: Varieties Ayamurasaki, Antin and local Purple Lampung. Ayamurasi is the introduction of the Japanese varieties, Antin was the result of the assembly and Purple Balitkabi Malang local is local varieties Lampung. To know the character of the growth and yield of sweet potato are three clones in acidic soil, it is necessary to test for these clones. This study was conducted at California State-owned plantation practices Lampung from May to November in 2011. The study used a randomized complete group (RKTL). Three clones of sweet potato used is Ayamurasaki Clones, Clone-1 and Clone Antin Local Purple Lampung, each repeated 4 times, so there are 12 experimental units. The data were analyzed by analysis of variance, and to know the difference between treatments done LSD a real level of 5% respectively. The conclusion of this research are: 1. There are differences between clones Antin agronomic character-1, Ayamurasaki, and Purple Local Lampung, 2. In acidic soil Lampung, Antin-1 clones are not resistant to stem borer attack and ladybugs (Omphisa anastomasalis), 3. Local Purple Clones Lampung has advantages in production and pest resistance, and has a good adaptation to the acidic soil Lampung, 4. Local Purple Lampung clones producing the highest production which amounted to 878.33 g per plant, followed by clones and clones Ayamurasaki Antin-1, each of which produces a production of 590 g and 166.67 g per plant Keywords: Character, Purple sweet potato, Acidic soil